Sensory allometry, foraging task specialization and resource exploitation in honeybees (2010)
Insect societies are important models for evolutionary biology and sociobiology. The complexity of some eusocial insect societies appears to arise from self-organized task allocation and group cohesion. One of the best-supported models explaining self-organized task allocation in social insects is the response threshold model, which predicts specialization due to inter-individual variability in sensitivity to task-associated stimuli. The model explains foraging task specialization among honeybee workers, but the factors underlying the differences in individual sensitivity remain elusive. Here, we propose that in honeybees, sensory sensitivity correlates with individual differences in the number of sensory structures, as it does in solitary species. Examining European and Africanized honeybees, we introduce and test the hypothesis that body size and/or sensory allometry is associated with foraging task preferences and resource exploitation. We focus on common morphological measures and on the size and number of structures associated with olfactory sensitivity. We show that the number of olfactory sensilla is greater in pollen and water foragers, which are known to exhibit higher sensory sensitivity, compared to nectar foragers. These differences are independent of the distribution of size within a colony. Our data also suggest that body mass and number of olfactory sensilla correlate with the concentration of nectar gathered by workers, and with the size of pollen loads they carry. We conclude that sensory allometry, but not necessarily body size, is associated with resource exploitation in honeybees and that the differences in number of sensilla may underlie the observed differences in sensitivity between bees specialized on water, pollen and nectar collection.